008 Neuropsychological advances in our understanding and classification of the dementias. Issue 10 (24th September 2010) - Snowden, J
Abstract : Abstract: The traditional conception of dementia is of a global impairment of intellect. A logical inference is that the dementia associated with distinct pathologies ought not to be differentiable on neuropsychological grounds. Yet, it is now clear that dementia comprises highly distinct profiles of cognitive and behavioural change, reflecting differences in the topographical distribution of cerebral pathology. These characteristic cognitive profiles can predict the nature of the underlying histopathology with a high degree of accuracy. In this talk I discuss neuropsychological profiling in Alzheimer's disease and other major forms of degenerative dementia, making reference to memory as well as to the cognitive domains of language, perception, spatial skills and executive functions and to behaviour and affect. I highlight the potential pitfalls in interpreting neuropsychological test data, which are particularly pertinent in the context of the dementias and which have clouded evaluation of dementia in the past. I show that there is no one-to-one correspondence between a neuropsychological test and a cognitive function or brain location and tests can potentially be failed for diverse reasons. I demonstrate the importance of examining test performance in the light of other tests and taking account of qualitative performance characteristics. I discuss phenotypic variation within Alzheimer's disease and its relationship to APOE status, and the neuropsychology of "focal" dementia syndromes, particularly frontotemporal dementia, semantic dementia and progressive aphasia. I show that the neuropsychological characteristics of patients can separate focal presentations of Alzheimer's disease from non-Alzheimer frontotemporal lobar degeneration. Moreover, neuropsychological phenotype has strong predictive value too in distinguishing τ from τ-negative, ubiquitin-positive histology, and even in separating sub-classes of ubiquitin histopathology. A prevailing assumption is that neuropathology provides the "gold-standard" for classification and understanding of disease. Yet, classification depends too on knowledge of the relationships between pathology and its clinical manifestation. Neuropsychology can play a crucial role in increasing understanding of the neurobiology of degenerative brain disorders and in the classification of the dementias. I conclude that dementia can best be regarded as a constellation of deficits, with patients showing both strengths (areas of relative preservation of function) as well as weaknesses. Different pathologies are associated with distinct and characteristic forms of dementia. The notion of dementia as generalised intellectual impairment should be abandoned.